Faktor-Faktor yang Memengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan di Kabupaten Bangka Barat - Reisty Amelia; Hakim, Dedi Budiman; Feryanto (Jurnal Paradigma Ekonomika, 2024)
Property tax is a tax whose management has been transferred from the central government to regional governments as a follow-up to the regional autonomy policy. The regional autonomy policy will be successful if the regions have the financial capacity and ability to develop the potential that exists in the regions. The purpose of this study was to determine the factors that influence taxpayer compliance in paying PBB-P2 in West Bangka Regency. The data analysis method of this study used multinomial logistic regression analysis with primary data sources obtained from 100 respondents. The results showed that the variables that influence the taxpayer's decision to pay taxes but not on time rather than not paying are age, education, income, and employment of government employees and tax services. The variables that influence the taxpayer's decision to pay taxes on time rather than not paying taxes are the work of government employees, tax sanctions, and tax services.